The Government of Urban Land: Representations, Joint and Action Strategies by State Actors - Gargantini, Daniela Mariana; Martiarena, Miguel Ángel; D'Amico, Desiree Alda (Universidad del Rosario, 2018)
Urban conflicts refer to social realities resulting from verifiable material situations, but these often remain dormant if they are not socially posed as problems. Their social performance and installation on the public agenda depends on the ways in which the different social actors define problematic situations and identify strategies to solve them. Because of its essential role in achieving decent housing and inclusion in the city, land access is one of the main urban conflicts. For this reason, considering the representations and interaction-action networks of actors involved in it is a way to promote and enhance the understanding of the looks and ways to solve the problems that determine the physical and symbolic production of the city. This article presents the progress of the study on the government of urban land in Córdoba Capital (Argentina). Although this research considers the representations of the social actors involved (state, economics and community actors), this paper only exposes the representations of state actors involved, their logical of understanding and action and relationships related to this conflict. The aim is to contribute towards the understanding of the complexity of the problems associated with access, control and governance of urban land by facilitating their visibility and the proposal of solving strategies.